Long runout landslides: a solution from granular mechanics - Parez, Stanislav; Aharonov, Einat (Frontiers in Physics, 2015)
Large landslides exhibit surprisingly long runout distances compared to a rigid body sliding from the same slope, and the mechanism of this phenomena has been studied for decades. This paper shows that the observed long runouts can be explained quite simply via a granular pile flowing downhill, while collapsing and spreading, without the need for frictional weakening that has traditionally been suggested to cause long runouts. Kinematics of the granular flow is divided into center of mass motion and spreading due to flattening of the flowing mass. We solve the center of mass motion analytically based on a frictional law valid for granular flow, and find that center of mass runout is similar to that of a rigid body. Based on the shape of deposits observed in experiments with collapsing granular columns and numerical simulations of landslides, we derive a spreading length Rf V^1/3. Spreading of a granular pile, leading to a deposit angle much lower than the angle of repose or the dynamic friction angle, is shown to be an important, often dominating, contribution to the total runout distance, accounting for the long runouts observed for natural landslides.